Semiparametric regression for the applied econometrician - Yatchew, Adonis (Themes in modern econometrics., 2003)
This book provides simple and flexible (nonparametric) techniques for analyzing regression data. It includes a series of empirical examples including estimation of Engel curves and equivalence scales, scale economies, household gasoline consumption, housing prices, option prices and state price density estimation.